International Classification of Functioning in professional rehabilitation: instruments for assessing work disability - Juliana Scholtão Luna; Gina Torres Rego Monteiro; Rosalina Jorge Koifman; Anke Bergmann (Revista de Saúde Pública)
ABSTRACT OBJECTIVE To review the main instruments of functional assessment and health status cited in the literature to evaluate Brazilian workers and verify the compatibility of their items with the core set for professional rehabilitation. METHODS A review of the literature was conducted in the main databases in search of articles that used assessment instruments in populations of workers between 2007 and 2017. Subsequently, the contents of the identified instruments were retrieved, and two evaluators analyzed their items to verify the compatibility with the categories of the core set of the International Classification of Functioning for professional rehabilitation. Cohen’s kappa coefficient was used to evaluate the agreement between the evaluators. RESULTS Five specific and eight generic instruments were selected to evaluate the functioning of workers. The analysis of the items of the total instruments allowed the definition of 58 categories (64.5%) of the core set with minimal overlap: 13 (76.5%) of the body functions component, 29 (72.5%) of the activities and participation component and 16 (49%) environmental factors. CONCLUSIONS The association of several instruments requires time and makes it difficult to use the classification. The development of instruments with direct association with its categories is essential to operationalize it.